Efforts to increase public awareness and resilience during the Covid-19 pandemic in Dringu District, Probolinggo - Candra, Sulis Dyah; Suharsono, Judi; Rohmah, Wilda Awaliatul Santi; Attijani, Ahmad; Wahyuningsasi, Evi Wulandari (Universitas Muhammadiyah Magelang, 2021)
The effects of the Covid-19 pandemic are quite large for the people in Dringu District, Probolinggo. The region holds the record for the highest number of positive patients and deaths. Service activities through thematic KKN are intended to contribute educating and empowering the community to reduce the transmission of the Covid-19 virus and increase the economic resilience of SMEs during the pandemic. Some of the efforts carried out are socializing the dangers of Covid-19 through banners and pamphlets, distributing masks, distributing hand sanitizers, spraying disinfectants and distributing nutritious drinks to increase immunity. Meanwhile, SME development is carried out to improve product branding, marketing through the marketplace and social media, and administering business permits.